Working with addicts: satisfactions and dissatisfactions - Didonet, Arne Carine Hartmann; Fontana, Rosane Teresinha (Rev Rene, 2011)
This is a descriptive, qualitative study which aims to investigate satisfactions and dissatisfactions of the team of workers in a Psychosocial Attention Center and the interface of experience in their personal lives. Data were collected in the first half of 2009, through a questionnaire given to 16 workers in a service located within the Rio Grande do Sul and analyzed using thematic analysis. It was found out that most of the difficulties and dissatisfactions experienced are directly related to users’ motivation to treatment, at relapse and dropouts. The satisfactions are related to the recovery of the user, as well as socializing and sharing experiences with colleagues. There was commitment of professionals with the treatment of subjects to seek ways of improving quality of life.